Respiratory symptoms and lung function in patients treated for pulmonary tuberculosis in Malawi: a prospective cohort study. Issue 11 (22nd December 2021) - Nightingale, Rebecca; Chinoko, Beatrice; Lesosky, Maia; Rylance, Sarah J; Mnesa, Bright; Banda, Ndaziona Peter Kwanjo; Joekes, Elizabeth; Squire, Stephen Bertel; Mortimer, Kevin; Meghji, Jamilah; Rylance, Jamie
Abstract : Rationale: Pulmonary tuberculosis (PTB) can cause post-TB lung disease (PTLD) associated with respiratory symptoms, spirometric and radiological abnormalities. Understanding of the predictors and natural history of PTLD is limited. Objectives: To describe the symptoms and lung function of Malawian adults up to 3 years following PTB-treatment completion, and to determine the evolution of PTLD over this period. Methods: Adults successfully completing PTB treatment in Blantyre, Malawi were followed up for 3 years and assessed using questionnaires, post-bronchodilator spirometry, 6 min walk tests, chest X-ray and high-resolution CT. Predictors of lung function at 3 years were identified by mixed effects regression modelling. Measurement and main results: We recruited 405 participants of whom 301 completed 3 years follow-up (mean (SD) age 35 years (10.2); 66.6% males; 60.4% HIV-positive). At 3 years, 59/301 (19.6%) reported respiratory symptoms and 76/272 (27.9%) had abnormal spirometry. The proportions with low FVC fell from 57/285 (20.0%) at TB treatment completion to 33/272 (12.1%), while obstruction increased from and 41/285 (14.4%) to 43/272 (15.8%) at 3 years. Absolute FEV1 and FVC increased by mean 0.03 L and 0.1 L over this period, but FEV1 decline of more than 0.1 L was seen in 73/246 (29.7%). Higher spirometry values at 3 years were associated with higher body mass index and HIV coinfection at TB-treatment completion. Conclusion: Spirometric measures improved over the 3 years following treatment, mostly in the first year. However, a third of PTB survivors experienced ongoing respiratory symptoms and abnormal spirometry (with accelerated FEV1 decline). Effective interventions are needed to improve the care of this group of patients.